The Determinants of Young Firms Growth in Tunisia - Hassan Arouri; Adel Ben Youssef; Francesco Quatraro; Marco Vivarelli (Institute of Labor Economics (IZA), 2018)
The aim of this paper is to investigate the growth dynamics of young small firms (in contrast with larger and older incumbents) in a developing country context, using a unique and comprehensive dataset of non-agricultural Tunisian companies. Our results suggest that significant differences between young and mature firms can be found as far as the drivers of their growth are concerned. The key finding being that - while consistently with the extant literature Gibrat's law is overall rejected - the negative impact of the initial size is significantly larger for young than mature firms. This result has interesting policy implications: since smaller young firms are particularly conducive to employment generation, they can be considered good candidate for targeted accompanying policies addressed to sustain their post-entry growth.
Keywords: O12; L26; 330; Tunisia; Gibrat's law; young firms; firm's growth